The Bible in Afrikaans: A direct translation – A new type of church Bible - Merwe, Christo H. J. van der (HTS teologiese studies, 2012)
Translating the Bible so that target audiences can easily understand the meaning of the text has dominated the theory and practice of Bible translation since the 1960s. Source oriented translations that are typically associated with word-for-word translations received little theoretical reflection. However, developments in Translation Studies have made it clear that the latter type of translations do not provide the type of equivalence more conservative churches really call for. The story of the Bible in Afrikaans relates to how the Bible Society of South Africa (BSSA) has taken seriously the needs of churches in South Africa for a source- oriented translation and teamed up with scholars to develop an academically justifiable model for a new type of church Bible. The functionalist model of Christiane Nord (1997) was used as point of departure and complimented by that of Ernst-August Gutt (2000). Pointing out the accomplishments and challenges of this pioneering project, this article paves the way for a scholarly discourse on source-oriented translations of the Bible.